Effects of substrate shock on release of AHL signals in ANAMMOX granules and properties of granules. Issue 4 (27th February 2019) - Zhang, Jing; Zhang, Ya-chao; Wang, Xiu-jie; Li, Jun; Zhou, Rong-xuan; Wei, Jia; Liang, Dong-bo; Zhang, Kai
Abstract : This study investigated the effects of substrate shock on the release of N -acyl-homoserine lactones (AHLs) in ANAMMOX granules and the relationship between AHL release, extracellular polymeric substance (EPS) excretion and the properties of granules. Abstract : This study investigated the effects of substrate shock on the release of N -acyl-homoserine lactones (AHLs) in ANAMMOX granules and the relationship between AHL release, extracellular polymeric substance (EPS) excretion and the properties of granules. In this study, a transient high total nitrogen (TN) concentration of 2100 mg L −1 for 24 h stimulated a rapid increase in N -hexanoyl-dl -homoserine lactone (C6-HSL) and N -octanoyl-dl -homoserine lactone (C8-HSL) in ANAMMOX granules resulting in abundant EPS excretion and deterioration of granule settleability. Substrate shock didn't affect the distribution of AHLs in the system. C8-HSL was dominant in the biomass phase without EPS and C6-HSL was dominant in the EPS phase and the biomass phase without EPS. The results of the batch tests also confirmed that the high substrate concentration can stimulate the release of abundant C8-HSL and C6-HSL. Loosely-bound EPS (LB-EPS) excretion was closely related to the content of C8-HSL. A significant increase in C8-HSL from 222.6 to 1124.7 ng L −1 occurred when the substrate concentration increased from 200 to 1200 mg L −1, leading to excessive accumulation of LB-EPS, which was considered the key factor for the deterioration of granule stability after substrate shock. C6-HSL could stimulate the granule activity. Substrate shock triggered the release of abundant C8-HSL, leading to excessive accumulation of EPS, in which C6-HSL was dominant. So C6-HSL increased significantly after substrate shock, serving to maintain bacteria activity. From the perspective of AHL-based quorum sensing, this study confirmed that excessive EPS are usually excreted under extreme environmental stress to protect bacteria activity while this self-defense behavior also results in unstable reactor operation performance.